Implementasi Problem Based Learning (PBL) Untuk Meningkatkan Pembentukan Karakter Sikap Peduli Lingkungan Pada Siswa Kelas V SD - Nadia Tia Lestari; Irma Nabilla Setiawan; Silvia Julianti (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to explain the application of the problem based learning model in developing environmentally conscious characters in fifth grade elementary school students. The method applied in this study is descriptive qualitative which allows researchers to gain insight into social phenomena that arise during the learning process. Data collection and processing are carried out through observation, interviews, and open questionnaires. The research findings indicate that the PBL model plays a role in increasing student participation in the learning process and building environmentally conscious characters through real activities such as maintaining cleanliness, saving energy, waste management and participating in preserving the environment. The application of PBL encourages students to think critically, work together, and put forward creative solutions to environmental problems. Thus, the use of the PBL approach has proven effective as a method for instilling environmentally conscious characters since the elementary education stage.